Evaluasi Kebijakan Pengelolaan Wilayah Pesisir Berbasis Pembangunan Berkelanjutan di Pantai Ngliyep Kabupaten Malang (Studi pada Dinas Pariwisata dan Kebudayaan Kabupaten Malang) - Rimadevi, Galuh; Mindarti, Lely Indah; Hanafi, Imam (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
This paper aims to determine the results of the policy evaluation of the coastal area management program based on sustainable development in Ngliyep Beach Kedungsalam Village Malang East Java Indonesia. This study used a case study design and it was conducted at the Department of Tourism and Culture of Malang Regency to find out the implementation of the program whether they were at the right target of the coastal communities in Ngliyep Beach. The results of this study indicate that related parties actively participate in developing coastal areas in Malang Regency. The Head of Ngliyep Beach Management keeps trying to maximize tourism promotion through various media. The Ngliyep Beach tourism can highly increase the economic activity of the people in this village including providing employment opportunities and preserving the culture and traditions of the local community.